Who owns responsibility? An administrator's take on implementing time-variable medical training in teaching hospitals. (3rd August 2019) - van Rossum, Tiuri R.; Scheele, Fedde; Bank, Lindsay; Sluiter, Henk E.; Heyligers, Ide C.
Abstract: Introduction: Developments in outcome-based medical education led to the introduction of time-variable medical training (TVMT). Although this idea of training may be a consequence of competency-based training that calls for individualized learning, its implementation has posed significant challenges. As a new paradigm it is likely to have repercussions on the organization of teaching hospitals. The purpose of this study is therefore to explore how hospital administrators cope with this implementation process. Methods: We conducted an exploratory qualitative study for which we interviewed administrators of hospitals who were actively implementing TVMT in their postgraduate programs. Results: Several problems of implementation were identified: existing governance structures proved unfit to cope with the financial and organizational implications of TVMT. Administrators responded to these problems by delegating responsibilities to departments, reallocating tasks, learning from other hospitals and scaling up their teaching facilities. Conclusions: Hospital administrators perceived the implementation of TVMT as challenging. TVMT affects the existing equilibrium between education and clinical service. Administrators' initial attempts to regain control, using steering strategies that were based on known concepts and general outcomes, including cutting departmental budgets did not work, nor did their subsequent wait-and-see approach of leaving the implementation to the individual departments.